Pengaruh Senam Lansia Terhadap Kualitas Tidur Pada Lansia Dengan Hipertensi di Kelurahan Apela 1 Kota Bitung - Minar Hutauruk; I Made Rantiasa; Nurlela Hi. Baco (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Introduce Elderly exercise is a form of physical exercise that has a good influence on the level of physical ability of the elderly, increases relaxation and helps improve sleep quality, especially in elderly people with hypertension. The purpose of this research was to find out the effect of elderly exercise on the sleep quality of the elderly with hypertension in the Apela I Village, Bitung. This research was conducted in the Apela I Village, Bitung from June to July 2022. The population were the elderly with hypertension, amounted to 15 respondents. This research used a pre experimental method with one group pretest-posttest design. Samples were taken using a purposive sampling. Data collection was done by giving questionnaires and then was processed by running the SPSS computer program version 16.0 to be analyzed by a Mc Nemar test with the significance level ? = 0,05. From the Mc Nemar test, it was obtained that the ? value = 0,000 < ? = 0,05. Meaning there is an effect of elderly exercise on the sleep quality of the elderly with hypertension in the Apela I Village, Bitung. The conclusion of this research is that there is an effect of elderly exercise on the sleep quality of the elderly with hypertension in the Apela I Village, Bitung. It is expected that this result will serve as basic knowledge for students and useful for further developments in the nursing field.